TEST-RETEST RELIABILITY OF AN ELITE ATHLETE–QUESTIONNAIRE FOR THE EVALUATION OF TRAINING-RELATED INJURY RISK FACTORS. Issue 7 (11th March 2014) - Wang, VC; Ottawa, F; Mayer, F; Wippert, PM
Abstract : Background: Since the 2009 International Olympic Committee consensus statement, health promotion and injury prevention has been of prime importance in the health care of elite athletes. However, to date, most studies investigating injury risk factors of elite athletes have focused on single causes of injury while the elite athletes' injuries are often multi-factorial determined. To get a more comprehensive understanding of the risk factors for injury, two multiple-perspective (medical/ psychosocial/training) questionnaires were developed to assess sport injury risk factors of elite athletes in two countries (Germany and Taiwan). Objective: To investigate test-retest reliability of an elite athlete questionnaire in two countries before conducting the official survey. This contribution focus on the presentation of the adopted IOC consensus statement tools like the medical Periodical Health Examination (PHE) and the Pre-Participation Evaluation (PPE). Design: Retrospective and cross-sectional. Setting: Anonymous participation of national level Olympic sport athletes. The survey consisted of 8 sections assessing Periodical Health Examinations & Pre-Participation Evaluation, Injuries (CIRS), Medical Care, Medical Support Quality, Health Behaviors, Training Environment, Life Events (ILE) and Subjective Stress (PSS). Participants: 63 athletes (35 Germans: 19f, 16m, 21.5±3.5 yrs; 28 Taiwanese: 3f, 25m, 23±2.8 yrs) training background of 2–3hrs/2–3times/week, filled out the questionnaire twice with a one-week interval. Risk factor assessment: A coding plan was developed. For the PPE and the PHE only numerical-scale data were analyzed by calculating Spearman's Rho tests between 1 st and 2 nd sets of answers on each question from all participants of same version. Statistical significance was set at ɑ=0.05. Results: Correlation analyses revealed good reliability levels ranging from r=.72 to r=.98 between the 2 tests. Conclusions: In general, the questionnaire part assessing PPE and PHE is a reliable instrument to use in German and Taiwanese athletes.